2011
DOI: 10.1007/s11748-011-0836-7
|View full text |Cite
|
Sign up to set email alerts
|

Graft selection in elderly patients undergoing coronary artery bypass grafting

Abstract: The clinical and angiographic outcomes after CABG in elderly patients were almost identical to those in nonelderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…The internal thoracic artery is considered to be the most reliable revascularization graft for diseased coronary arteries because of its long-term durability [15]. The left internal thoracic artery is usually used for revascularization of the left anterior descending coronary artery, even in elderly patients [16]. In the present study, 64% of patients in each group had lesions in the left anterior descending artery.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The internal thoracic artery is considered to be the most reliable revascularization graft for diseased coronary arteries because of its long-term durability [15]. The left internal thoracic artery is usually used for revascularization of the left anterior descending coronary artery, even in elderly patients [16]. In the present study, 64% of patients in each group had lesions in the left anterior descending artery.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, we believe that improvements in surgical techniques, critical care medicine and rehabilitation care may contribute to achieving equivalent outcomes in both elderly and non-elderly patients. The use of internal thoracic artery grafts may also contribute to improved long-term outcomes in both elderly and non-elderly patients [16].…”
Section: Adult Cardiacmentioning
confidence: 99%
“…Although use of the internal thoracic artery favors long-term survival in these patients [19], one of many issues which remains unresolved is the importance of complete revascularization. Comparably excellent graft patency can be achieved between elderly and nonelderly patients [51]. Kozower et al [52] found diminished survival in octogenarians with incomplete revascularization, whereas Mohammadi et al [53] more recently reported just the opposite.…”
Section: Long-term Survivalmentioning
confidence: 99%
“…Не приходится удивляться сопоставимыми значени-ями прогноза у больных через год после КШ, поскольку недавно было показано, что проходимость шунтов через год после операции составляла 91,6% среди больных до 75 лет и 89,3% среди пациентов 75 лет и старше (р=0,28) [8]. Более важными прогностиче-скими факторами оказались распространенность коронарного и некоронарного атеросклероза, выра- женность дислипидемии, наличие систолической дис-функции левого желудочка, что вполне ожидаемо.…”
Section: Discussionunclassified